Evaluasi Vaksinasi pada DOC (Day Old Chick) Parent Stock di PT S.I.P. - Faizah, Nurul; Lestari, Ayu; Abidin, A. Mustika (Universitas Islam Negeri Alauddin Makassar, 2025)
In order to support the improvement of poultry performance, one key supporting factor is livestock health management. This study aims to evaluate vaccination management on Cobb strain parent stock chicken farms at PT S.I.P., Gowa Regency. This study uses a qualitative descriptive method with a field observation approach and interviews with related parties in the company. The data collected were analyzed based on three main parameters, namely the time, method, and dose of vaccine administration, then compared with relevant reference standards. The results of the study indicate that the vaccination program implemented at PT S.I.P. has complied with applicable regulations. Vaccination is carried out at the right time, with the appropriate administration method and dose for each type of vaccine, such as IB, Reo, Gumboro, ND-IB, ND-AI, and Fowl Pox vaccines. During the observation period, no chicken deaths were found due to disease, indicating the success of the vaccination program implemented. Evaluation of the timing, method, and dose of vaccine administration showed high compliance with scientific references and modern livestock industry practices.